2006
DOI: 10.1080/10245330500469841
|View full text |Cite
|
Sign up to set email alerts
|

Duffy blood group and malaria

Abstract: Very important progress has been made over the last years in understanding the Duffy blood group system and its complexity. The Duffy blood group antigen serves not only as blood group antigen, but also as a receptor for a family of proinflammatory cytokines termed chemokines, and as a receptor for Plasmodium vivax malaria parasites. The Duffy antigen has been termed the "Duffy Antigen Receptor for Chemokines" (DARC) or the Duffy chemokine receptor. DARC might play a role as a scanvenger on the red blood cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 64 publications
1
60
0
1
Order By: Relevance
“…The DARC locus shows complex genetic signatures of positive natural selection, 27,28 and it has been suggested that the Ϫ46C allele has arisen under the selective pressure of an ancestral form of malaria that also used DARC but was more lethal than P vivax, which is generally not associated with mortality and is no longer very common in Africa. 20 Interestingly, neutropenia is commonly observed during malaria and is more common in infection with P vivax than P falciparum, 29,30 and there is clinical and experimental evidence that neutrophils contribute to the adverse outcomes after malarial infection. [31][32][33][34][35] Furthermore, a genomewide analysis of the host response to malaria also implicates neutrophilmediated pathways in underlying malarial pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DARC locus shows complex genetic signatures of positive natural selection, 27,28 and it has been suggested that the Ϫ46C allele has arisen under the selective pressure of an ancestral form of malaria that also used DARC but was more lethal than P vivax, which is generally not associated with mortality and is no longer very common in Africa. 20 Interestingly, neutropenia is commonly observed during malaria and is more common in infection with P vivax than P falciparum, 29,30 and there is clinical and experimental evidence that neutrophils contribute to the adverse outcomes after malarial infection. [31][32][33][34][35] Furthermore, a genomewide analysis of the host response to malaria also implicates neutrophilmediated pathways in underlying malarial pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…DARC is expressed mainly on the surface of red blood cells (RBCs) and endothelial cells, where it binds multiple chemokines that have relevance to both HIV pathogenesis (eg, RANTES and MCP-1) and neutrophil biology (eg, GRO␣). 18,19 The Ϫ46T3C polymorphism is specific to persons of African ancestry, 10,[20][21][22] and homozygosity for the Ϫ46C allele (Ϫ46C/C genotype) abrogates DARC expression on erythrocytes. [18][19][20] Because DARC on RBC serves as a receptor for the malarial protozoa Plasmodium vivax, 19,20 Duffynull status (DARC Ϫ46C/C genotype) on RBC is associated with a selective advantage against this form of malaria.…”
Section: Introductionmentioning
confidence: 99%
“…The Duffy antigen system consists of multimeric erythrocytic membrane surface proteins composed of different subunits in which glycoprotein D is the major subunit that carries the antigenic determinants as defined by anti-Fy(a), anti-Fy(b) antibodies (Tournamille et al, 1997). The Duffy antigen system achieved considerable prominence when it was discovered that it comprised the erythrocytic receptor site for binding and entry of merozoites of Plasmodium vivax and Plasmodium knowlesi into erythrocytes (Langhi & Bordin, 2006;Miller et al, 1976). Individuals lacking the Duffy phenotype were also found to be resistant to infection by strains of malaria that bind to Duffy antigen on erythrocytes, thus explaining the remarkable resistance to P. vivax malaria that occurs in large areas of West Africa.…”
Section: Duffy Blood Group Antigen On Erythrocytesmentioning
confidence: 99%
“…3 It also acts as a docking site for the malarial species Plasmodium vivax, and this is believed to have driven the emergence of the DARC-null state (ie, erythrocytes lacking DARC) common among persons with sub-Saharan African ancestry. 4 DARC could impact on HIV pathogenesis in a number of ways. First, DARC binds several of the chemokine ligands for CCR5, the critical coreceptor for HIV entry into cells.…”
Section: Hiv: Getting To the Heart Of Darcness ----------------------mentioning
confidence: 99%
“…It is well known that DNA methyltransferases interact not only with HDACs but also with various histone methyltransferases and, as such, it is reasonable to expect that interfering with one epigenetic mark will impact other marks. 4,5,8 The full extent of this interaction in vivo in human patients has yet to be explored.…”
mentioning
confidence: 99%